2022
DOI: 10.1002/ddr.21932
|View full text |Cite
|
Sign up to set email alerts
|

Hirudin attenuates puromycin aminonucleoside‐induced glomerular podocyte injury by inhibiting MAPK‐mediated endoplasmic reticulum stress

Abstract: Damage to podocytes is an important determinant of renal pathology. The puromycin aminonucleoside (PAN) mice nephropathy model is commonly used in the study of renal disease with podocyte injury. Hirudin has a broad nephroprotective effect and has been shown to treat renal interstitial fibrosis in previous studies. Mice were given PAN by gavage to prepare animal models, and MPC5 cells were incubated with PAN in vitro. Twenty-four hours urine was collected for analysis of urinary protein levels. Renal pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…It plays a crucial role in processes such as autophagosome formation and the transmission of oxidative and in ammatory signals [40]. In models of kidney disease, when external stimuli exceed the ER's steady-state, there is a signi cant increase in ER stress (ERS), which disrupts cytoskeletal proteins in podocytes [41]. ER dysfunction is associated with systemic lupus erythematosus (SLE), wherein enhancing the suppressive capacity of regulatory T cells (Tregs) can mitigate disease activity by inhibiting ERS.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial role in processes such as autophagosome formation and the transmission of oxidative and in ammatory signals [40]. In models of kidney disease, when external stimuli exceed the ER's steady-state, there is a signi cant increase in ER stress (ERS), which disrupts cytoskeletal proteins in podocytes [41]. ER dysfunction is associated with systemic lupus erythematosus (SLE), wherein enhancing the suppressive capacity of regulatory T cells (Tregs) can mitigate disease activity by inhibiting ERS.…”
Section: Discussionmentioning
confidence: 99%
“…It also mitigated the disruption of cytoskeletal proteins (synaptopodin, nephrin, and podocin), activation of endoplasmic reticulum stress (ERS), and apoptosis in both PAN mice and podocytes induced by PAN. This effect was achieved through the inhibition of p38 MAPK signaling-mediated ERS [ 80 ]. All evidence supports the protective effect of hirudin against podocyte injury.…”
Section: Hirudin In Ckdmentioning
confidence: 99%
“…[79] Inhibiting p38 MAPK signaling-mediated ERS [80] Acute kidney injury Inhibiting the interactions between thrombin and PAR [81] Table 2. Cont.…”
Section: Diabetic Nephrologymentioning
confidence: 99%
“…Another study indicated that hirudin increases the expression of podocalyxin and GLEPP1 in the apical region of podocytes under high glucose conditions, thus shielding podocytes and maintaining the integrity of the glomerular filtration barrier's structure and function (7). In puromycin aminonucleoside (PAN) mouse models and PAN-induced podocyte models, hirudin protects the kidneys and prevents proteinuria by suppressing the transmission of the p38 MAPK signaling pathway, reducing endoplasmic reticulum stress in podocytes, and attenuating the damage to the cytoskeletal proteins of podocytes by PAN (8).…”
Section: Protection Of Podocytesmentioning
confidence: 99%